Mimara Museum, Zagreb 04 - Bernard Gagnon (Wikimedia Commons, 2019)
Notice iconographique issue de Wikimedia Commons. Titre: Mimara Museum, Zagreb 04. Madonna and Child with John the Baptist by RaffaelliNo del Garbo, Mimara Museum, Zagreb
Droits : Licence Creative Commons Attribution-Share Alike 4.0 via Wikimedia Commons
Keywords: œuvre d'art; tableau; sculpture; statue; wikimedia commons; Peintures